7-Chloroquinolin-4-yl Arylhydrazone Derivatives: Synthesis and Antifungal Activity - Auri R. Duval; Pedro H. Carvalho; Maieli C. Soares; Daniela P. Gouvêa; Geonir M. Siqueira; Rafael G. Lund; Wilson Cunico (The Scientific World Journal)
Fifteen 7-chloro-4-arylhydrazonequinolines have been evaluated for their in vitro antifungal activity against eight oral fungi: Candida albicans, C. parapsilosis, C. lipolytica, C. tropicalis, C. famata, C. glabrata, Rhodutorula mucilaginosa, and R. glutinis. Several compounds exhibited minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) activities comparable with the first-line drug fluconazole. These results could be considered as an important starting point for the rational design of new antifungal agents.